Effects of prepartum ruminally protected choline supplementation on performance of beef cows and calves - L.A. Pacheco; L.R. Hibbard; M.J. Macek; N.A. Sproul; G.J. Eckerle; E.A. Bailey; J.W. Bolte; John R. Jaeger; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2011)
Prepartum supplementation of spring-calving beef cows is a vital part of cow-calf enterprises, often affecting subsequent reproductive success. Most research in the area of prepartum supplementation has focused on provision of either energy or protein; only modest attention has been given to the use of supplemental micronutrients. One such micronutrient is choline. Choline is classified generally as a B vitamin and is an essential nutrient. Phosphatidylcholine and other choline-containing lipids maintain the structural integrity of cellular membranes and play a vital role in metabolism of dietary fat. Choline-containing phospholipids are also important precursors for intracellular-messenger molecules and cell-signaling molecules critical to the reproductive process. Choline is commonly found in feedstuffs and forages but is highly degradable in the rumen. For choline supply to be increased effectively, it must be offered in a form that is resistant to ruminal digestion. This can be achieved by encapsulating choline in lipid. Therefore, the objective of our study was to evaluate the effect of prepartum ruminally protected choline supplementation on cow and calf performance.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen' s Day; 2011; Beef; Choline; Performance; Calves